2022
DOI: 10.5336/dentalsci.2021-86502
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Squamous Cell Carcinoma Based on a Chronic Denture Irritation

Abstract: Oral squamous cell carcinoma (OSCC), the sixth most-common head and neck neoplasm, constitutes more than 80% of all malignancies found in the oral cavity. 1 OSCC is usually seen in middle-aged and older individuals. Its prevelance in males is slightly higher than in females. Although it can occur in all sites of the oral cavity such as the mucosal sides of cheeks, lips or the palatal regions, the most common occurance area is the posterolateral ventral side of the tongue. 2 Consuming alcohol and tobacco, long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…In contrast, Zokaee et al reported an increased frequency of potentially malignant lesions on the tongue [9]. Although oral squamous cell carcinoma (OSCC) may develop on the cheeks, lips, or palate, the tongue is the most frequent location [24]. In this study, OSCC was most commonly observed in the lower lip and tongue.…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, Zokaee et al reported an increased frequency of potentially malignant lesions on the tongue [9]. Although oral squamous cell carcinoma (OSCC) may develop on the cheeks, lips, or palate, the tongue is the most frequent location [24]. In this study, OSCC was most commonly observed in the lower lip and tongue.…”
Section: Discussioncontrasting
confidence: 59%